Price Setting in a Model with Production Chains : Evidence from Sectoral Data - Shamloo, Maral (IMF Working Papers; Working Paper, 2010)
Reconciling the high frequency of price changes at the micro level and their apparent rigidity at the aggregate level has been the subject of considerable debate in macroeconomics recently. In this paper I show that incorporating production chains in a standard New- Keynesian model replicates two stylized facts about the data. First, sectoral prices respond with significantly different speeds to aggregate shocks. Meanwhile, the responses to sectorspecific shocks are similar. Second, the standard price setting models are unable to quantitatively match the amount of monetary non-neutrality observed in the data. I argue, First, that the input-output linkages in production generate different responses to aggregate shocks across sectors. Second, calibrating this model to the US data can create five times more monetary non-neutrality in response to nominal shocks compared to an equivalent homogeneous economy with intermediate inputs. Finally, the model implies that upstream industries respond faster to aggregate shocks compared to downstream industries. I show that this prediction is supported by the data.